Pengaruh Penyuluhan Demonstrasi SADARI Terhadap Tingkat Pengetahuan Tentang Pemeriksaan Payudara Sendiri Pada Siswi Kelas X Di SMA N 1 Godean Kabupaten Sleman - Poppy Kurniawati; Evi Wahyuntari (Bunda Edu-Midwifery Journal (BEMJ), 2025)
According to data from the Global Burden of Cancer Study in 2020, the number of new breast cancer cases in Indonesia reached 68,858 (16.6%) out of a total of 396,914 new cancer cases. The prevalence of cancer in Yogyakarta Province exceeded the national average, standing at 4.1 per 1,000 population, which made it the highest in Indonesia. In 2023, Sleman experienced a significant surge in breast cancer cases, with 1,040 new cases recorded within a year. The total number of breast cancer cases in Sleman Regency reached 2,045. Among adolescents aged 15–19 in Sleman Regency, 30 new breast cancer cases were reported in 2023. This study aims to examine the effect of Breast Self-Examination (SADARI) counseling through demonstrations on the level of knowledge of 10th- grade female students at SMA Negeri (State Senior High School) 1 Godean. This study employed quantitative approach with pre-experimental design using one-group pretest-posttest model. The sample consisted of 45 respondents, selected through total sampling. The instrument used was a questionnaire on Breast Self-Examination (SADARI). The results of the Wilcoxon statistical test showed an Asymp. Sig. (2- tailed) value of 0.000. Since the value is less than 0.05, it can be concluded that "Ha is accepted," which indicates a significant effect of the SADARI demonstration counseling on the level of knowledge among 10th-grade female students at SMA Negeri 1 Godean.